Sovereign credit ratings, foreign participation and bond yields in selected African countries - Rusike, Tatonga Gardner (My University, 2020)
The thesis investigates two main themes-the influence of changes in foreign participation and sovereign ratings on local currency and Eurobond yields. As background analysis, we first explored the development of local currency government bond markets in Africa through a literature survey. The theoretical discussion builds on the concept of original sin developed by Eichengreen and Hausmann (1999) and proposes a modified way of measuring original sin. We then examine whether changes in foreign participation impact bond yields and volatility in six African countries employing a battery of econometric techniques in both panel and time series settings. We establish that increase in foreign participation reduces bond yields confirming the benefits of investor base diversification. Other than the level of foreign participation, we also observe that the lag of bond yields, policy interest rate, inflation, exchange rate and global policy rate are significant variables explaining the behaviour of bond yields in the group. However, the impact on bond yields volatility is mixed. While increasing foreign participation has no impact on volatility in the group setting, isolating South Africa shows that changes in foreign participation do impact on the volatility of bond yields. Thus, increasing foreign participation in South Africa does come with a cost of higher bond yields volatility. The second theme addresses the political economy of sovereign credit ratings in Africa and empirically examines the impact of changes in sovereign credit ratings on bond yields using event study and panel vector auto-regressions techniques. The political economy analysis reflects that while credit rating agencies have faced global criticisms, there are Africa specific challenges. Using tests on ratings accuracy and ratings failures, we showed that African countries have higher default rates than global averages. Our data on African sovereign ratings show that credit rating agencies failed during the 2011 Arab spring and the 2014 oil price fall. Our event study analysis reflects that only close to a third of rating actions directly impact bond yields. The empirical analysis largely suggests that changes in sovereign ratings are no longer unanticipated, and not carrying much new information
Sovereign credit ratings, foreign participation and Euro and domestic bond yields in Sub-Saharan Africa
A thesis submitted to the Graduate School of Business Administration of the University of the Witwatersrand in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Finance, 2020
Keywords: Africa; Bond yields; Bond market development; Credit rating agencies; Eurobonds; Foreign participation; Political economy; Original sin and sovereign credit ratings; UCTD; SDG-8: Decent work and economic growth